Shape-Controlled Nanoparticles in Pore-Confined Space - Knossalla, Johannes; Paciok, Paul; Goehl, Daniel; Jalalpoor, Daniel; Pizzutilo, Enrico; Mingers, Andrea M.; Heggen, Marc; Dunin-Borkowski, Rafal E.; Mayrhofer, Karl; Schueth, Ferdi; Ledendecker, Marc (Journal of the American Chemical Society, 2018)
Increasing the catalyst's stability and activity are one of the main quests in catalysis. Tailoring crystal surfaces to a specific reaction has demonstrated to be a very effective way in increasing the catalyst's specific activity. Shape controlled nanoparticles with specific crystal facets are usually grown kinetically and are highly susceptible to morphological changes during the reaction due to agglomeration, metal dissolution, or Ostwald ripening. A strong interaction of the catalytic material to the support is thus crucial for successful stabilization. Taken both points into account, a general catalyst design is proposed, combining the enhanced activity of shape-controlled nanoparticles with a pore-confinement approach for high stability. Hollow graphitic spheres with narrow and uniform bimodal mesopores serve as model system and were used as support material. As catalyst, different kinds of particles, such as pure platinum (Pt), platinum/nickel (Pt3Ni) and Pt3Ni doped with molybdenum (Pt3Ni-Mo), have exemplarily been synthesized. The advantages, limits and challenges of the proposed concept are discussed and elaborated by means of time-resolved, in and ex situ measurements. It will be shown that during catalysis, the potential boundaries are crucial especially for the proposed catalyst design, resulting in either retention of the initial activity or drastic loss in shape, size and elemental composition. The synthesis and catalyst design can be adapted to a wide range of catalytic reactions where stabilization of shape-controlled particles is a focus.